Effect and Mechanism of Soluble Dietary Fiber from Corn Bran on Loperamide-induced Constipation in Mice - Xiangrui ZENG; Caixia JIANG; Xiaolan LIU; Xiqun ZHENG; Xuyao WEI (Shipin gongye ke-ji)
This study was performed to elucidate effects of corn bran soluble dietary fibers (CSDF) on loperamide-induced constipation and changes in intestinal flora in mice. Sixty male BALB/c mice were randomly divided into a normal group, a model group, CSDF low, medium, and high dose groups (3, 6, and 12 g·kg−1·d), and a combination group (CSDF: Lactobacillus paracasei=30:1(v:v)), with 10 mice in each group. CSDF was administered for 14 d. At the end of the intervention, constipation was induced with single dose administration of a loperamide suspension (10 mg·kg−1), and mice were monitored for 7 d. Compared with the model group, CSDF intervention significantly shortened the time to the first black stool in constipated mice. The volume of defecation spanning 6 h and the water content of feces were also significantly increased (P<0.05). Small bowel propulsion rate and colon pathology experiments showed a 110.58% increase in small bowel propulsion rate, and a 43.67% increase in colonic crypt depth in the combined group compared with that of the model group. Compared to that of the model group, the levels of gastrointestinal tract-related neurotransmitters (motilin, 5-hydroxytryptamine, etc.) were elevated in mice that received CSDF, suggesting that CSDF could alleviate constipation in enteric nervous system disorders. CSDF supplementation also increased the abundance of beneficial gut bacteria (Bifidobacterium, Lactobacillus, and Lachnospiraceae) and elevated levels of short chain fatty acids (SCFAs), with typical SCFAs (acetic, propionic, and butyric acids) reaching 1.89-, 1.60-, and 4.35-fold higher levels, respectively, in the L-CSDF group than that in the model group. In conclusion, CSDF can alleviate constipation by regulating neurotransmitter levels and remodeling intestinal flora and metabolite levels, and its efficacy in alleviating constipation-induced colonic inflammation can be enhanced by administration in combination with probiotics.